2005
DOI: 10.1055/s-2005-872416
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Efficacy of Nonablative Long-Pulsed 1064-nm Nd:YAG Laser Treatment of Wrinkles Compared at 2, 4, and 6 Months

Abstract: Rhytides represent an aesthetic problem for a large percentage of the population. Many methods, both noninvasive and invasive, have been used for the treatment of wrinkles. Recently, the long-pulsed 1064-nm Nd:YAG laser has been shown to enhance dermal collagen synthesis without damaging the epidermis. The purpose of this preliminary study is to evaluate the use of the long-pulsed Nd:YAG laser in the nonablative treatment of periocular and perioral wrinkles. Ten patients with facial wrinkles were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 15 publications
0
44
1
Order By: Relevance
“…The first mechanism involves discrete cellular damage caused by direct absorption in hemoglobin, melanin, and water during each pulse and bulk heating from cumulative pulsing in a region. As a result, damage created through direct absorption and through sustained time at elevated temperature initiates a healing response, prompting collagen stimulation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The first mechanism involves discrete cellular damage caused by direct absorption in hemoglobin, melanin, and water during each pulse and bulk heating from cumulative pulsing in a region. As a result, damage created through direct absorption and through sustained time at elevated temperature initiates a healing response, prompting collagen stimulation [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed the findings that PDL treatment of sun-damaged skin can lead to improvements in wrinkles with histological evidence [10][11][12][13][14][15]. Long pulsed 1,064-nm Nd:YAG laser with its low scattering coefficient and weak absorption by water and melanin has also been shown to improve the appearance of coarse wrinkles and fine lines and to reduce skin laxity [16][17][18][19][20]. Rapid sequences of long 1,064-nm pulses (0.3 ms) enable a large area to be covered quickly by multiple passes, causing diffused general heating of the upper dermis and thus stimulating a wound healing response and collagen remodeling.…”
Section: Introductionmentioning
confidence: 70%
“…The large scattering coefficient of the 1,320-nm Nd:YAG laser causes the thermal energy to disperse laterally within the dermis, inducing a large volume of dermal injury relative to the beam size [23]. For the long-pulsed 1,064-nm laser, since the main target is protein with water as a secondary target, the heating effect in the target tissue absorbing the 1,064-nm beam is non-specific [20]. In addition, because of the scattering effect of tissue at this wavelength, the area of the highest photon density, and thus the photo-thermal effect, is not at the surface of the tissue, but some 1-2 mm below the surface [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have documented new collagen formation following exposure to this wavelength, resulting in the clinical improvement in rhytids and photorejuvenation (4,5).…”
Section: Introductionmentioning
confidence: 98%